A Study of Language Learning Strategy Use among Indonesian EFL University Students - Rianto, Agus (UIN Salatiga, 2020)
This study investigated the use of language learning strategies among 329 Indonesian undergraduate students in their English as foreign language learning. The Strategy Inventory for Language Learning (SILL) Version 7.0 for ESL/EFL learners developed by Oxford was employed to measure the students’ EFL learning strategies based on gender, study program, and English proficiency differences. A descriptive analysis and an independent t-test were used to analyze the collected data. The findings showed that the female, the social science, and the higher English proficiency students used overall language learning strategies more frequently in their EFL learning. Metacognitive was the strategy category most used by the students and compensation was the least used one. The memory, cognitive, metacognitive, affective, and social strategy categories were used at a high level and the compensation strategy category, at a moderate level. Although there were significant differences in the use of overall strategy and strategy categories between males and females and between social science and science students, no significant differences were found in use between students with lower and higher English proficiency. The findings had several practical implications in the process of EFL learning, especially in the higher education context. Keywords: Language Learning Strategy, English Proficiency, Gender, SILL, Study Programs